Legal Protection in Foreign Exchange Trading Activities with Profitable Strategies - Heryanty Hasan (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
Foreign exchange trading is used free floating system and does not use fixed rate system or fixed exchange rate as stipulated at the International Conference "The Bretton Woods". In foreign exchange trading can be classified as several active actors who conduct foreign exchange transactions, namely central banks, individuals or public companies, brokers or brokers, governments, speculators and arbitrators. The purpose of this study is to provide the public with an understanding of the legal basis of implementing foreign exchange trading and the legal protection provided to traders for their profitable strategies in trading foreign exchange based on Indonesian positive law. This normative legal research examines the problem of norms in the form of blurred norms based on the use of a statutory approach. Based on the results of the study conducted, it was found that the legal basis for the implementation of foreign exchange is the Commodity Futures Trading Law and further regulations stipulated by the Head of BAPPEBTI, including the Head of BAPPEBTI Regulation No. 109 / BAPPEBTI / PER / 01/2014 j.o Head of BAPPEBTI Regulation No. 95 / BAPPEBTI / PER / 06/2012. Then concerning guaranteeing legal protection for a profitable trading strategy in forex trading, it can be protected as a trade secret through the Trade Secret Law so that forex traders can file a lawsuit to the District Court for violations of the forex trading strategywhich is owned by a trader to be asked for termination of actions and /or compensation (vide Article 11 of the Trade Secret Law).